1989
DOI: 10.2105/ajph.79.8.1048
|View full text |Cite
|
Sign up to set email alerts
|

Use of smokeless tobacco, cigarette smoking, and hypercholesterolemia.

Abstract: The primary purpose of this study was to determine the extent to which regular use of smokeless tobacco is associated with hypercholesterolemia (2 6.2 mmol/L) among 2,840 adult males. The confounding effects of age, education, physical fitness, body fatness, and other tobacco use were also examined. After adjustment, smokeless tobacco users were 2.5 times, heavy smokers were 2 times and mild/moderate smokers were 1.5 times more likely to have hypercholesterolemia than non-users of tobacco. Cigarette smokers di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 23 publications
5
31
0
1
Order By: Relevance
“…Thesites usedfor theassessment of bodyfat wereas follows: for males(a)thigh-anterior aspectmidway between the hip and the knee (verticalfold), (b) chest-half the distancebetweenthe anterioraxillaryline and the nipple (diagonal fold),and(c)abdomen-taken laterally ata distance of2 cm from the umbilicus (vertical fold); forfemales(a) 2.5 em above the iliac crest (diagonal fold), (b) back of the arm midway betweenthe shoulderand elbow (verticalfold), and (c) thigh-anterior aspect midway between the hip and the knee (vertical fold). Indirect validation of the body fat assessment showed substantial relationships with measured cardiovascular fitness in the present study and with age, television viewing, exercisehabits,andhypercholesterolemia in other studies (Tucker, 1989;Tucker & Friedman, 1989).…”
Section: Methodssupporting
confidence: 77%
See 2 more Smart Citations
“…Thesites usedfor theassessment of bodyfat wereas follows: for males(a)thigh-anterior aspectmidway between the hip and the knee (verticalfold), (b) chest-half the distancebetweenthe anterioraxillaryline and the nipple (diagonal fold),and(c)abdomen-taken laterally ata distance of2 cm from the umbilicus (vertical fold); forfemales(a) 2.5 em above the iliac crest (diagonal fold), (b) back of the arm midway betweenthe shoulderand elbow (verticalfold), and (c) thigh-anterior aspect midway between the hip and the knee (vertical fold). Indirect validation of the body fat assessment showed substantial relationships with measured cardiovascular fitness in the present study and with age, television viewing, exercisehabits,andhypercholesterolemia in other studies (Tucker, 1989;Tucker & Friedman, 1989).…”
Section: Methodssupporting
confidence: 77%
“…The test exhibitsa significantdegreeof predictiveutilityrelative to other more comprehensive measures of cardiovascular fitness,suchas treadmill testing(VOzmax) andthe 12-minrun (Kasch,Phillips,Ross, Carter,& Boyer, 1966;Nagle,Balke, & Naughton, 1965),whichare not practicalwhenevaluating over 8,000 subjects. Validity of the fitness measure was confirmed and afforded additional credence by the present study, since scores on the step test were highly related to gender, age,obesity, smoking, andexercisestatus,whileother research has provided similar indirect validation (Tucker, 1989;Tucker, in review;Tucker, Cole, & Friedman, 1986;Tucker& Friedman, 1989).…”
Section: Methodssupporting
confidence: 67%
See 1 more Smart Citation
“…In contrast, data from another large population-based study found that subjects who regularly used ST products had 2.5 times the prevalence of hypercholesterolemia (Ͼ6.2 mmol/L) compared with nonusers of tobacco. 63 Khurana et al 64 also found a relationship between chewing tobacco use and dyslipidemia. Tobacco chewers showed significantly decreased levels of HDL cholesterol and significantly increased levels of very low-density lipoprotein cholesterol and triglycerides.…”
Section: Additional Risk Factors For Cvdmentioning
confidence: 94%
“…Les études réalisées aux États-Unis chez les utilisateurs de snus retrouvent des résultats divergents selon l'âge des sujets, les perturbations lipidiques affectent les plus âgés [42]. Une augmentation du risque de diabète de type 2 corrélée à une consommation élevée de snus (OR = 2,7 ; IC95 % : 1,3-5,5) est constatée [43].…”
Section: Facteurs De Risque Cardiovasculaireunclassified